Factors Affecting the Employability of Final-Year Undergraduate Students in Kunming, China - Yang, Yang (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The study examines the key determinants influencing the employability of final-year undergraduate students at YTB University, Kunming, China. This research integrates multiple theoretical frameworks and empirical literature to construct a comprehensive model that explores the impact of Communication Skills, Academic Performance, Social Mobility Skills, and General Attitude on graduates’ employability. Research design, data and methodology: The study employed a quantitative approach with a multi-stage sampling technique to ensure a representative sample across four majors. The primary data collection instrument was a 5-point Likert scale questionnaire, validated through expert assessment and a pilot test to ensure reliability. 360 completed questionnaires were analyzed to test the proposed hypotheses and explore the causal relationships between the identified factors and graduate employability. Results: The research findings confirmed that Communication Skills, Academic Performance, Social Mobility Skills, and General Attitude significantly influence the employability of final-year undergraduate students. The results demonstrated substantial effects of these factors on graduates' workforce readiness, reinforcing their critical role in preparing students for labor market integration. Conclusions: The empirical findings underscore the need for higher education institutions to enhance academic training, career development programs, and skill-building initiatives that address labor market expectations.